Introduction to the Special Section: Strengthening Institutional Collaboration for Development and Economic Growth - Andreas Klasen (Global Policy, 2019)
Open markets, international trade and foreign direct investments (FDI) are a source of prosperity in challenging times. This Special Section looks at developed economies and emerging markets, also taking into account the role of trade for impactful capacity-building in Least developed countries (LDCs). Specific emphasis is placed on financing economic development and trade, analysing what roles trade and development finance should play in the quest for an efficient mobilisation of private capital for growth, trade and development.
Keywords: 320